Code-Switching Used by Mrs. EE, the Owner of N Store, to Her In-Store Customers - Catherine Catherine; Flora Debora Floris (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This study utilized the theoretical frameworks presented by Wardhaugh (2006) and Appel and Muysken (2005) to analyze the kinds and functions of code-switching utilized by Mrs. EE, the owner of N Store, when communicating with customers. This study utilized a qualitative approach that examined Mrs. EE’s use of code-switching in her speech. The study’s results showed that Mrs. EE utilized both situational and metaphorical kinds of code-switching. She utilized various code-switching functions namely referential, directive, expressive, phatic, metalinguistic, and poetic. The study has concluded that Mrs. EE’s use of code-switching may be influenced by various factors such as her linguistic background, the context of the conversations, and her relationship with her customers.